B-Cell-Activating Factor Affects the Occurrence of Thyroid Autoimmunity in Chronic Hepatitis C Patients Treated with Interferon Alpha. (27th February 2012) - Kajiyama, Yusuke; Kikuchi, Kentaro; Takai, Atsuko; Hosoya, Naomi; Hoshino, Hiromi; Hino, Kunihiko; Miyakawa, Hiroshi
Abstract : Chronic hepatitis C (CHC) patients frequently suffer from thyroid disorders during interferon therapy. However, the mechanism remains unclear. In this study, we investigated the association between serum B-cell-activating factor belonging to the TNF family (BAFF) levels and the presence of antithyroid peroxidase antibody (anti-TPO) in CHC patients treated with pegylated interferon alpha and ribavirin combination therapy. Six months after the therapy, anti-TPO antibody was detected in 10 (males, 1; females, 9) of 50 patients. The mean age of these patients was higher than that of the anti-TPO-negative patients (61 yr versus 55 yr). Before treatment, the serum BAFF levels of the anti-TPO-positive patients were higher than those of the anti-TPO-negative patients. After starting therapy, the serum BAFF levels of both the anti-TPO-positive and -negative patient groups were elevated. Our findings suggest that the serum BAFF concentration before therapy can predict the risk of thyroid autoimmunity in elderly female patients with CHC.